Analisis Aktivitas Belajar Siswa menggunakan Model Kooperatif Tipe Think Pair Share dengan Strategi Index Card Match - Najjah Wardiyatul Jannah; Martini Martini; Muhamad Arif Mahdiannur (Universitas Pahlawan, 2023)
This study aimed to determine the implementation of learning using a cooperative learning model type of think pair share (TPS) with an index card match (ICM) strategy. The research method used was observational research involving 32 students of 8th grade in one of the MTs in Mojokerto Regency. The data collection techniques in this study were observation of learning implementation. The research data were analyzed using percentage of learning implementation, and Cohen's Kappa coefficient (k). The results showed that the implementation of learning using a cooperative learning model type of TPS with an ICM strategy for two meetings was carried out with very good criteria, and the two observers still had a fair agreement in assessing the implementation of learning. Students are actively involved in the discussion process to complete tasks individually or in pairs. Based on these results, it can be concluded that the cooperative learning model type of TPS with ICM strategy can have an impact on student activity in the implementation of learning, although there are still limitations in the study.